2013
DOI: 10.5603/cj.2013.0077
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous versus intracoronary bolus of glycoprotein IIb/IIIa inhibitor administration during primary percutaneous coronary intervention on long-term left ventricular systolic and diastolic function

Abstract: Background: In primary percutaneous coronary intervention (PCI), glycoprotein (GP) IIb/IIIa inhibitors are often given in order to attain and maintain better myocardial perfusion. We tested the hypothesis that intracoronary (IC) bolus of GP IIb/IIIa inhibitors might produce a greater improvement in left ventricular (LV) systolic and diastolic function than an intravenous (IV) bolus. Methods and results: Seventy seven patients undergoing primary PCI for their first ST elevation myocardial infarction (STEMI) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Over the last decade, the best therapy for acute myocardial infarction (MI) has been PPCI to achieve full reperfusion and hence reduce mortality [20]. The benefits of PCI include increased myocardial blood flow and a normal TIMI flow grade, resulting in a lower risk of cardiovascular events [21]. When percutaneous coronary intervention is performed, the vascular complication becomes more prevalent, leading to a rise in the number of fatalities as well as an expensive burden on the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, the best therapy for acute myocardial infarction (MI) has been PPCI to achieve full reperfusion and hence reduce mortality [20]. The benefits of PCI include increased myocardial blood flow and a normal TIMI flow grade, resulting in a lower risk of cardiovascular events [21]. When percutaneous coronary intervention is performed, the vascular complication becomes more prevalent, leading to a rise in the number of fatalities as well as an expensive burden on the patient.…”
Section: Discussionmentioning
confidence: 99%
“…No beneficial effect of GP IIb/IIIa inhibitors in elderly patients can be the result of distal embolisation of coronary vessels or myocardial perfusion impairment (De Luca et al, 2014). Other researchers have found that GP IIb/IIIa inhibitors had meaningful influence on higher ejection fraction after STEMI (Pellicori et al, 2013).…”
Section: -Month Follow-upmentioning
confidence: 99%
“…Recently the topic of intracoronary use of abciximab has been extensively discussed in the literature [52][53][54][55][56]. This administration route seems to provide a much higher concentration of abciximab in the target area and possibly allow direct influence not only on the platelet GP IIb/IIIa receptor, but also on vitronectin and Mac-1 receptors, enhancing dose-dependent off-target effects of abciximab.…”
Section: Abciximabmentioning
confidence: 99%